Principal Management in Improving Teacher Professionalism in Elementary School - Junaedi, Agi; Asy’ari, Hasyim; Maknuun, Lu’lu’ Il (Journal of Education and Learning Innovation, 2024)
This research uses a type of qualitative research with a qualitative descriptive approach. The object of this research was carried out at SD Negeri Paripurna. Data collection techniques using Observation, Interview, and Documentation. Sources of data in this study included school principals, Deputy Head of Curriculum Affairs, PAI teachers, and class teachers at SD Negeri Paripurna. The analysis techniques used in this study are data collection, data reduction, data presentation, and conclusion. The triangulation used to test the validity of the data is technique and source triangulation. The results showed that (1) the management of the principal at SD Negeri Paripurna, Sumedang Regency, consisted of planning, organizing, implementing, and supervising. The planning carried out by the principal includes the school's vision and mission, and work programs to improve teacher professionalism. Implementation, the program carried out by the school principal, namely the implementation of the management strategy "Kudu nepi samẻmẻh indit" or "must arrive before leaving" implemented by the Principal of SD Negeri Paripurna has been communicated and understood by all implementing elements at SD Negeri Paripurna to build "management Happy Monday". The implementation of the HAPPY MONDAY Program is one of the programs to increase teacher professionalism (2) The steps taken by school principals to improve teacher professionalism are implementing the Happy Monday program which is scheduled once a week every Monday. Motivate and encourage continued education and participation in training activities or teacher competencies. teacher development through assignments.